An analytical study Of Vehicular Effects on Sound in Residential, Silent And Mixed zones Of Sylhet - Limon, Jafor Ahmed; A R M Kamruzzaman,; Ahmed, Fahad; Rahman, Md Mofizur; Hussain, Sharif (GUB Journal of Science and Engineering, 2024)
Noise is a form of environmental pollution that influences our life and comfort. Because of growing populations and increasing urbanization, noise is more common and is getting worse. Sylhet is one of the Bangladesh's most rapid growth cities. In recent years, it has experienced unprecedented population increase. During the past decades, there has been a noticeable growth in the number of individuals moving to Sylhet City from other regions of the nation, particularly for jobs and education. As the lifestyle and facilities of this city increase compared to the suburbs and countryside areas, nowadays vast amounts of individuals are interested in living in the Sylhet city. As the population is increasing, the number of transport facilities (volume of vehicles) are also increasing. To be more specific, the number of private cars ownership is increasing day by day. As a result, now the sound level is increasing much more than the standard level. Throughout the working days, between 6 am and 12 am, noise levels were monitored at 15 significant places (residential, silent and mixed zones) across the city. A sound meter was used to conduct the study. Vehicular data were converted to passenger car unit (PCU) conversion factor. Geometric design standard manual (LGED, 2005) was used to calculate PCU by passenger car factor or passenger car equivalent. “Environmental conservation rules-1997” was considered as basic to analyze the data. The study was conducted to quantify the amount of noise pollution that happens in the city's mixed, residential, and silent zones. It also revealed the impact of vehicular noise. It was found that most of the time the sound level at every site remained consistently much above the allowable limit and vehicular noise played a significant role in every case. GUB JOURNAL OF SCIENCE AND ENGINEERING, Vol 10(1), 2023 P 10-16